AMPLIFIKASI DAN ATENUASI GELOMBANG SEISMIK DI LAPISAN SEDIMEN PERMUKAAN - Urip Nurwijayanto Prabowo; Marjiyono Marjiyono; Sismanto Sismanto (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
Soft sedimentary layer caused the amplification effect which amplified seismic wave. Besides of that, the soft sedimentary layer also have atenuation effect of seismic wave propagation. This research was conductedto evaluated the amplification and attenuation effect in soft sedimentary layer based on theoritical evaluation and 176 microtremor datas of Denpasar city which analyzed using HVSR method. The results of this research show that the value of amplification have a linier relation with the quality factor that have negative correlation with attenuation. The quality factors that calculated from HVSR curves are the quality factor of secondary seismic wave propagation